Digitalizing the Narratives: Structural Analysis of Far Cry 3 - Ali, Eeshan; Karati, Arijit (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2015)
Every form has its own structure. Technically, though there is a difference between computer games and literature, but structurally both reflect same modes of the presentation which is carried out by certain codes. The present paper looks into the structural analysis of computer games with technical aspect as well as literature aspect with special reference to Far Cry 3, a first person action adventure computer game which received several awards and critically acclaimed for its graphics, story line, features etc. Besides this paper relocate Vladimir Propp’s theory of narrative function in Far Cry 3 and decode how the computer game with the help of certain binary opposition and codes have become one of the fundamental tools of getting entertained in the popular imagination.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé